The Mediating Role of Positive Emotion: The Influence of Visual Merchandising and Store Atmosphere on Impulse Buying: Study on KKV Store Consumers in Malang - Atiyystul Karimah; Yayuk Sri Rahayu (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2024)
This study examines and evaluates the effects of Visual Merchandising and Store Atmosphere on impulse purchasing behavior, mediated through Positive Emotions. Utilizing a quantitative methodology, the research focuses on consumers who have shopped at the KKV Store in Malang City. A sample of 145 individuals was generated based on Hair's formula, implementing a nonprobability sampling method with purposive criteria. Data collection was accomplished through offline questionnaires, and data analysis was conducted using smartPLS. The findings indicate that Visual Merchandising does not significantly impact Positive Emotions. In contrast, Store Atmosphere has a strong influence on Positive Emotions, which subsequently affects impulse purchasing decisions. While Visual Merchandising may not directly affect these purchasing choices, it is clear that Store Atmosphere plays a critical role in shaping them. Moreover, although Visual Merchandising does not influence impulse purchasing through Positive Emotions, Store Atmosphere is found to significantly affect impulse buying behavior through the mediation of Positive Emotions. The implications of this research are noteworthy for retailers and marketers. Understanding that Store Atmosphere has a strong effect on both Positive Emotions and impulse purchasing can guide KKV Store and similar establishments in designing their retail environments more effectively. Retailers should prioritize enhancing the Store Atmosphere through elements such as lighting, music, layout, and scents, as these aspects can create favorable emotional responses in consumers, ultimately leading to increased sales. Additionally, while Visual Merchandising strategies are essential, they should be complemented by a focus on the overall shopping environment to maximize their potential impact. In summary, this study contributes valuable insights into how emotional responses mediated by Store Atmosphere can drive impulse buying behavior, offering practical recommendations for improving retail strategies.